Association of Detrusor Muscular Activity With the Outcome of Transurethral Resection of Prostate in Patients With Severity of Bladder Outflow Obstruction (Bangladesh Journal of Urology, 2020)
Objective: To evaluate the association of detrusor muscular activity with outcome of TURP in patients with severity of bladder outflow obstruction.Methods: This is a hospital based cross sectional study conducted in the Department of Urology of Dhaka Medical College Hospital, Dhaka.Elderly male patients having lower urinary tract symptoms (IPSS=20-35) with no retention (non-catheterized patient), who attended in Dhaka Medical College Hospital, were included in the study. A total of 73 patients meeting the enrollment criteria were included in the study. They were evaluated by history, physical examination including DRE and necessary investigations to identify the potential candidates for TURP. Then the potential participants were counseled for Urodynamic study. All patients underwent TURP by expert surgeon. Three months after TURP, repeat Urodynamic study was done and the results were compared to see the outcome. Afterward the data were plotted for the clarification of detrusor contractility at three levels: normal detrusor contractility (voiding pressure 40-60cm of water), detrusor over activity (voiding pressure >60cm of water) and detrusor under activity (voiding pressure 40); equivocal(BOOI=20-40);Unobstructed(BOOId” 20) are taken into consideration. The test statistic used to analyze the data was descriptive statistics and ANOVA test. The level of significance was set at 0.05 and P